MODEL ISOTERM FREUNDLICH DAN LANGMUIR OLEH ADSORBEN ARANG AKTIF BAMBU ANDONG (G. verticillata (Wild) Munro) DAN BAMBU ATER (G. atter (Hassk) Kurz ex Munro) - Murtihapsari Murtihapsari; Bertha Mangallo; Dini Dwi Handyani (Universitas Nusa Bangsa, 2012)
Freundlich and Langmuir Isotherms Model by Active Chorcoal Adsorbent Bamboo Andong (G. verticillata (Wild) Munro) and Bamboo Ater (G. atter (Hassk) Kurz ex Munro) Diazinon insecticide adsorption by two types of adsorbent, namely activated charcoal bamboo andong (G. verticillata (Wild) Munro) and bamboo ater (G. atter (Hassk) Kurzex Munro) at optimum conditions determined the maximum adsorption capacity of both types of adsorbent. Data analysison the effect of concentration on the adsorption capacity was used Langmuir and Freundlich isotherms equation. It was obtained. That the curve of adsorption isotherms of the Langmuir isotherm better modeled with linear regression coefficients were relatively more approach 1 is R2 = 0,996 for both types of adsorbents. Langmuir isotherm equation obtained from adsorpsi maximum capacity of activated charcoal bamboo andong (G. verticillata (Wild) Munro) of 4.630 mg/g (1,433.10-5 mol/g) with K = 0,332 (Kmol/L)-1 and Eads at -2,750 kJ/mol, while the activated charcoal bamboo ater (G. atter (Hassk) Kurzex Munro) produce the maximum adsorption capacity of 1,786 mg/g (5,868.10-6 mol/g) with K = 0,202 (Kmol/L)-1 and Eads = -3,898 kJ/mol, so the adsorption of both types of adsorbents indicated experiencing a physical adsorption (physisorption / fisisorpsi).Keyword: G. verticillata (Wild) Munro, G. atter (Hassk) Kurz ex Munro, Adsorption, Diazinon, actived charcoal ABSTRAK Adsorpsi insektisida diazinon oleh dua jenis adsorben, yaitu arang aktif bambu andong (G. verticillata (Wild) Munro) dan bambu ater (G. atter (Hassk) Kurz ex Munro) pada kondisi optimum bertujuan untuk menentukan kapasitas adsorpsi maksimum dari kedua jenis adsorben. Analisis data pengaruh konsentrasi terhadap kapasitas adsorpsi digunakan persamaan isoterm Langmuir dan Freundlich. Berdasarkan data yang diperoleh, kurva isoterm adsorpsi lebih mengikuti model isoterm Langmuir dengan koefisien regresi linier yang relatif lebih mendekati 1 yaitu R2 = 0,996 untuk kedua jenis adsorben. Dari persamaan isoterm Langmuir diperoleh kapasitas adsorpsi maksimum arang aktif bambu andong (G. verticillata (Wild) Munro) sebesar 4,630 mg/g (1,433.10-5 mol/g) dengan K = 0,332 (Kmol/L)-1 dan Eads sebesar -2,750 kJ/mol, sedangkan arang aktif bambu ater (G. atter (Hassk) Kurz ex Munro) menghasilkan kapasitas adsorpsi maksimum sebesar 1,786 mg/g (5,868.10-6 mol/g) dengan K = 0,202 (Kmol/L)-1 dan Eads = -3,898 kJ/mol, sehingga adsorpsi kedua jenis adsorben diindikasikan mengalami adsorpsi secara fisik (physisorption/ fisisorpsi).Kata kunci : G. verticillata (Wild) Munro, G. atter (Hassk) Kurz ex Munro Adsorpsi, Diazinon, Arang aktif